IMPLEMENTASI PEMBELAJARAN RME ( REALISTIC MATHEMATIC EDUCATION ) TERHADAP PENALARAN DAN KEMAMPUAN MEMECAHKAN MASALAH MATEMATIKA SISWA KELAS V SDN KARANGAYU 02 SEMARANG - Joko Sulianto, Kurniawan Eko Prabowo (Universitas PGRI Semarang, 2013)
This research is motivated by the lack of reasoning and problem-solving skills math class V students on the subject of the story about the multiplication and division of fractions. Students are less able to understand and decipher the core issues contained in the matter of the story. In addition, students difficulty changing story problems into mathematical form. This makes the learning achievements of students who achieved less than the maximum.Issues examined in this study were (1) Is the mathematical reasoning fifth grade students Karangayu SD N 02 Semarang can reach the learning criterion was after receiving RME? (2) Is there any difference in the ability to solve mathematical problems Karangayu fifth grade students of SDN 02 Semarang after receiving RME learning?This research is quantitative. By using the design / design study pre-experimental design types of one- group pre-test-post-test design. Based on the pre-test and post-test reasoning variables obtained average value of 51.38 in the pre-test criteria for low and average value of the post-test 65.06 on the criterion of moderate / normal. The research hypothesis has been mentioned that, H01 is rejected and thank Ha1 the mathematical reasoning fifth grade students Karangayu SD N 02 Semarang reach criterion medium / normal after getting learning RME (Realistic Mathematic Education). While the t-test on the variable math problem-solving skills obtained t count> t table = 5.971> 2.021. The research hypothesis has been mentioned that, H01 and thank Ha1 denied that there are differences in the ability to solve mathematical problems graders V SD N Karangayu 02 Semarang after getting learning RME.